THE ROLE OF FINANCIAL MARKET REGULATION AND SUPERVISION IN STRENGTHENING FINANCIAL STABILITY (Global Conference on Multidisciplinary Research and Innovation, 2026)
Financial stability is a key condition for sustainable economic development and the resilience of national economies to internal and external shocks. In this context, effective regulation and supervision of financial markets play a decisive role in preventing systemic risks, ensuring transparency, and maintaining confidence in the financial system. This article examines the role of financial market regulation and supervision in strengthening financial stability. It analyzes regulatory frameworks, supervisory mechanisms, and macroprudential policies aimed at mitigating financial risks. The study highlights the importance of balanced regulation that supports financial development while preventing excessive risk-taking. The findings suggest that strong regulatory institutions and effective supervision significantly contribute to financial stability and long-term economic sustainability.
Keywords: Financial stability; Financial market regulation; Financial supervision; Macroprudential policy; Systemic risk; Economic stability